TENNANTITE DECOMPOSITION: EVIDENCE FROM THE KEDABEK COPPER DEPOSIT, AZERBAIJAN - Bortnikov N.S.; Genkin A.D.; Troneva N.V. (My University, 1992)
A microscopic study of ores of the Kedabek deposit revealed unusual microtextures of intimate intergrowths of fine grains of chalcopyrite, fahlore (tetrahedrite), arsenopyrite and sphalerite. These textures result from fahlore (tennantite) decomposition. A detailed study of the chemical composition of earlier and later generations of ore minerals and the bulk composition of the products of decomposition of tennantite suggest that the decomposition of tennantite is due to an increase in the activity of antimony. The reason for such an increase is the crystallization of earlier generations of arsenopyrite and tennantite which caused a depletion of arsenic and an increase in the antimony/arsenic ratio in residual solutions.